Efeito antitumoral in vitro do óleo essencial de Melaleuca alternifolia no câncer de mama - Assmann, Charles Elias (2017)
Introduction: Breast cancer is the neoplasia with the highest incidence and mortality among women in the world after non-melanoma skin cancer. Tumor progression is classified into different stages, from 0 to IV. At stage III, cancer can spread through the mammary and adjacent tissues, leading to the development of Locally Advanced Breast Cancer (LABC). LABC can evolve from swelling and redness in the mammary tissue to the formation of wounds and exposed lesions. Although several therapeutic strategies being used to treat LABC, patient’s survival is low and topical treatments are not well studied. Thus, the search for new therapeutic agents is needed. In this sense, Melaleuca alternifolia essential oil, also known as tea tree oil (TTO), which has demonstrated antiproliferative action on breast cancer in a previous study can be mentioned. Other important properties are also related to TTO, such as anti-inflammatory, antibacterial and antifungal activity, as well as antitumor effect on melanoma cell lines. Objectives: The aim of this study was to perform a literature review about epidemiological and physiopathological aspects of LABC and to evaluate the antitumor effect in vitro of M. alternifolia essential oil on breast cancer, as well as its toxicity on normal cells. Materials and Methods: The literature review realized to assess epidemiological and physiopathological parameters, as well as diagnosis and treatment aspects related to LABC was based on the search of scientific articles published in PUBMED-MEDLINE database in the last 10 years. Further, an in vitro study using three cell lines: breast cancer cells (MCF-7), fibroblasts (HFF-1) and Peripheral Blood Mononuclear Cells (PBMCs) was performed. MCF-7 cells were exposed to different TTO concentrations to investigate antitumor capacity (1, 3, 10, 30, 100, 300 e 1000 μg/mL). Several parameters were investigated: cell viability and proliferation, apoptotic pathway, gene expression and cell cycle modulation, cell growth curve and colony formation assays were also performed using spectrophotometric, fluorimetric and molecular analysis. Moreover, cytotoxicity parameters for healthy cells (HFF-1 e PBMCs) exposed to different TTO concentrations (100, 300, 600 e 1000 μg/mL) were also performed. Results: Regarding the literature review conducted, the results indicated that breast cancer progression at this stage does not have effective topical or palliative treatment and that conventional chemotherapies are not effective and have a large set of side effects. In the in vitro study, we observed that TTO concentration of 1000 μg/mL showed strong cytotoxic and antiproliferative activity in MCF-7 cells. Results of the apoptotic and gene regulatory analysis indicated that the concentration of 300 μg/mL induced apoptosis due to the expression of genes related to programmed cell death. Furthermore, colony formation and cell growth analyzes showed a great TTO antiproliferative capacity and cell cycle analyzes revealed arrestment of cells in the S phase. Complementary cytotoxicity analyzes performed using healthy cell lines indicated that TTO concentration of 1000 μg/mL showed to be cytotoxic for both cells. However, TTO concentration of 300 μg/mL was able to induce cellular proliferation of fibroblasts after 72 hours of exposure, demonstrating some possible mechanism of protection of the essential oil. Moreover, TTO at low concentrations did not present toxicity for both cell lines. Conclusions: The results suggest that M. alternifolia essential oil has antitumor activity on the MCF-7 breast cancer cell line without cytotoxic effects at low concentrations for healthy cells. In this way, the oil could be used for the development of new therapeutic agents to the use, mainly topical, for CMLA. Thus, it would be possible to increase the survival and/or the quality of life of patients affected by the disease.